2008
DOI: 10.1128/aac.00149-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Profiling of Ceftaroline against a Collection of Recent Bacterial Clinical Isolates from across the United States

Abstract: This study evaluated the in vitro activity of ceftaroline, a novel cephalosporin with broad-spectrum activity against gram-negative and -positive pathogens, against 4,151 recent clinical isolates collected in the United States. Ceftaroline was very potent against bacteria found in community-and hospital-acquired infections, including methicillin-resistant Staphylococcus aureus, multidrug-resistant Streptococcus pneumoniae, and common Enterobacteriaceae spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
93
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 20 publications
13
93
0
3
Order By: Relevance
“…It exhibits bacterial killing against our laboratory-derived ampicillin-resistant E. faecium mutant that overproduces the wild-type PBP5. Such a profile differs from those of most E. faecium clinical isolates, which were reported as resistant to all ␤-lactams, including ceftaroline (6). Like other cephalosporins, ceftaroline is not indicated for treatment of enterococcal infections.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…It exhibits bacterial killing against our laboratory-derived ampicillin-resistant E. faecium mutant that overproduces the wild-type PBP5. Such a profile differs from those of most E. faecium clinical isolates, which were reported as resistant to all ␤-lactams, including ceftaroline (6). Like other cephalosporins, ceftaroline is not indicated for treatment of enterococcal infections.…”
mentioning
confidence: 57%
“…It is inhibited by ceftaroline, the active metabolite of the prodrug ceftaroline fosamil, which was recently approved by the U.S. Food and Drug Administration (FDA) for use in adult patients with acute bacterial skin and skinstructure infections and community-acquired bacterial pneumonia and more recently approved by the European Medicines Agency (EMA) for similar indications (10, 11). Previous studies have reported that ceftaroline had poor inhibitory activity against ␤-lactam-resistant E. faecium strains, all of which were expected to possess a PBP5 protein (6,12). To better understand these differences, we have characterized the interaction between a wild-type form of PBP5 and ceftaroline.…”
mentioning
confidence: 99%
“…Ceftaroline fosamil, a prodrug, is rapidly converted via plasma phosphatase enzymes to its bioactive metabolite, ceftaroline (1). Ceftaroline exhibits broad-spectrum bactericidal in vitro activity against Grampositive organisms, including those with contemporary resistant Gram-positive phenotypes, such as methicillin-resistant Staphylococcus aureus (MRSA) and penicillin-resistant Streptococcus pneumoniae, as well as common Gram-negative pathogens (2,3). Like other ␤-lactam antimicrobials, the activity of ceftaroline is due to inhibition of penicillin-binding proteins, which are involved in the biosynthesis of the bacterial cell wall.…”
mentioning
confidence: 99%
“…Yine Avrupa ve Amerika'da komplike cilt enfeksiyonu etkeni olarak tanımlanan 246 MRSA suşunun dahil edildiği çalışmalarda ise MİK 50 , MİK 90 ve MİK aralığı sırasıyla 0.5 µg/ml, 0.5 µg/ml ve 0.25-2 µg/ml olarak bildirilmiştir 10,11 . Bu konuda yapılan diğer çalışmalarda seftarolin MİK 90 değerleri 0.5 µg/ml 12 , 1 µg/ml 13,14 ve 2 µg/ml [15][16][17] . Bizim çalışmamızda, cilt enfeksiyonlarından izole edilen MRSA suşları dışında kan ve solunum yolu kültürlerinden izole edilen suşlar da kullanılmıştır.…”
Section: Discussionunclassified